2019
DOI: 10.1186/s12245-019-0247-6
|View full text |Cite
|
Sign up to set email alerts
|

To enhance the quality of CPR performed by youth layman

Abstract: Background By educating laymen, survival after cardiac arrest can increase in society. It is difficult to reach the entire population with cardiopulmonary resuscitation (CPR) training. However, if 15% of the population knows how to perform CPR, an increase in short- and long-term survival in patients suffering a cardiac arrest could be seen. To educate youth is a way to reach parts of the population. This study aimed to investigate the effect of a 2-h CPR intervention for youth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
8
1
2
Order By: Relevance
“…This increase is a small improvement of the youths' self-confidence in performing mouth to mouth ventilation. In real life events, there is a possibility for a high psychological barrier of youth to initiate mouth-to-mouth ventilation [27] resulting in en poorly performed ventilation of the patient [28]. Schroeder et al [29], therefore, argues that, due to the decreasing importance of mouth-to-mouth ventilation in lay resuscitation in favor of chest compressions, specially adapted CPR-algorithms for school children could be discussed [29].…”
Section: Discussionmentioning
confidence: 99%
“…This increase is a small improvement of the youths' self-confidence in performing mouth to mouth ventilation. In real life events, there is a possibility for a high psychological barrier of youth to initiate mouth-to-mouth ventilation [27] resulting in en poorly performed ventilation of the patient [28]. Schroeder et al [29], therefore, argues that, due to the decreasing importance of mouth-to-mouth ventilation in lay resuscitation in favor of chest compressions, specially adapted CPR-algorithms for school children could be discussed [29].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness of BLS was present in 66.6% of students, but skills were found in 18% only. [12] Furthermore, healthcare professionals and international studies also reported that trained individuals were more willing and confident to perform bystander CPR [7]. Therefore, trained professionals or students may be able to perform early CPR, initiate resuscitation efforts, and speed up access to prehospital and definitive care.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the apps was that the compression site was inconsistently labeled, leading to inaccurate hand and arm positions. According to a study conducted in 2019, consistency with hand and arm positions is critical for chest compression accuracy [76]. According to the CPR guidelines [9,10,[48][49][50], chest compressions should be at least 5-6 cm in depth, at a rate of 100-120 compressions per minute (2 per second).…”
Section: Chest Compressionmentioning
confidence: 99%
“…However, ventilation volume and verification of chest rising are poorly integrated into the ventilation part of CPR. A study from 2019 indicated that teaching schoolchildren ventilation requires more teaching time, and it is harder to establish good quality BLS results [76]. Apps that teach ventilation as a part of CPR are more time-consuming; however, they also adhere more closely to the BLS guidelines.…”
Section: Ventilationmentioning
confidence: 99%